The Implementation of SAK ETAP to The Financial Report of SMEs - Nur Fani Arisnawati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This study aims to determine the preparation of Financial Report based on SAK-ETAP and constraints on the preparation of Batik Ar-Radhah SMEs in Pekalongan City. This research method uses a qualitative approach. This study uses primary data on the SMEs Batik Ar Radhah Pekalongan City. Data collection techniques using triangulation techniques, namely participant observation, interviews, and documentation. The sample in this study was selected based on a purposive sampling collection technique. Data analytic technique with data reduction, data display, and conclusions. The results of the study are the financial statement components in SMEs Batik Ar-Radhah Pekalongan City are slightly different when compared to the financial statement format with SAK ETAP chassis. The financial format according to Batik Ar-Radhah Pekalongan CitySMEs is current assets, trade receivables and other receivables, trade payables, short-term liabilities, and equity. In SAK ETAP regulates the existence of current assets: cash and cash equivalents, inventories; non-current assets, short-term liabilities, and long-term liabilities and equity. Constraints faced due to the lack of human resources in the field of financial accounting and financial report socialization based on SAK-ETAP by the Pekalongan City Government through training. So the suggestion from the author, it is better if human resources must be supported by its quality. For example: providing scholarships for employees of S1 Accounting / S1 Management education; employees are involved in training activities from Disperindagkop and other institutions.